Casa come bene e casa come servizio: dalle i-stanze familiari alla (i)stanza dell’individuo - Pozzi, Gianluca; Mombelli, Elena; Vignati, Giulia (Mechane, 2023)
The transformation of the house from an asset to a service is making important changes in contemporary housing models: these modifications are here investigated from a psychological and architectonical point of view. Starting from the relationship between these changes and their repercussions on the public and private life, original interpretations and design guidelines are provided to support a balanced growth of the inhabitants.